Book review: J. Judd Owen: Making Religion Safe for Democracy: Transformation from Hobbes to Tocqueville. - Bejan, T (Cambridge University Press, 2016)
Making Religion Safe for Democracy tackles an increasingly important—and frustratingly familiar—question for our “postsecular” age. Can liberal democracy be reconciled with religion, especially when that religion is muscular, energized, and no longer content to remain in the private sphere? And, perhaps even more pressing for those of our profession, as Owen puts it in the introduction: “Is political theory, and in particular liberal political theory, as we find it today capable of responding, or even grasping what is at stake"?